Benefits of Pair Work Activity in Speaking Class: A Narrative Review - Subarnin, Cian; Abidin, Azwar; Atikah, Dewi (IAIN KENDARI, 2025)
This narrative review investigates the benefits of pair work activities in EFL speaking classes. The data for this study were drawn from 25 selected articles published between 2013 and 2023. The research explores four main themes related to pair work in EFL speaking: language development through practice, social and emotional support in learning environments, active engagement and participative learning, and effective pedagogical strategies. The conclusions drawn from the 25 articles reveal several benefits of pair work activities, including language development through practice (enhancing speaking proficiency and facilitating vocabulary acquisition), social and emotional support in learning environments (encouraging peer feedback, creating a supportive learning environment, reducing anxiety, and increasing confidence), active engagement and participative learning (promoting active student engagement and increasing participative learning), and effective pedagogical strategies (the teacher's role in enhancing pair work effectiveness and effective task structuring). The research suggests that integrating pair work activities into EFL speaking instruction can significantly improve language learning outcomes. Furthermore, EFL teachers can effectively utilize pair work to enhance students' speaking abilities, boost their confidence, and improve overall language proficiency. Keywords: benefits of pair work; collaborative learning; EFL speaking; language development.